2000
DOI: 10.1017/s0022112000001221
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and direct numerical simulation of the flow at a gravity-current head. Part 1. Flow topology and front speed for slip and no-slip boundaries

Abstract: Direct numerical simulations are performed of gravity-current fronts in the lock-exchange configuration. The case of small density differences is considered, where the Boussinesq approximations can be adopted. The key objective of the investigation is a detailed analysis of the flow structure at the foremost part of the front, where no previous high-resolution data were available. For the simulations, high-order numerical methods are used, based on spectral and spectral-element discretizations and compact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

54
391
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 400 publications
(451 citation statements)
references
References 36 publications
54
391
1
Order By: Relevance
“…At 10T, five vortices develop, and the left and right gravity current frontal heads move to the locations x/H = −6.47 and 6.7, respectively. The vortex numbers, locations of the gravity current frontal heads, and asymmetry of the speed of the left and right gravity current frontal heads compare well with those presented in Figure 11 of Härtel et al [2000].…”
Section: A "Lock Exchange" Problemsupporting
confidence: 75%
“…At 10T, five vortices develop, and the left and right gravity current frontal heads move to the locations x/H = −6.47 and 6.7, respectively. The vortex numbers, locations of the gravity current frontal heads, and asymmetry of the speed of the left and right gravity current frontal heads compare well with those presented in Figure 11 of Härtel et al [2000].…”
Section: A "Lock Exchange" Problemsupporting
confidence: 75%
“…The development of gravity currents is typically an unsteady phenomenon, i.e., current kinematics and the inner density distribution are time varying, therefore the lockexchange setup is a simple and convenient way to investigating the flow features of these particular currents. Numerical modeling has also been used to investigate the evolution and impact of gravity currents [2,10,13,23,27,[33][34][35]44,47,59]. Although the motion of these currents is invariably three-dimensional, laboratory experiments and numerical results indicate that the large-scale features may be reasonably well described through a two-dimensional approach [27].…”
Section: Introductionmentioning
confidence: 99%
“…He also said that the characteristic head would control the mixing behavior, current velocity, and current profile. The current induced mixing is considered to be caused by two types of instabilities: billows, and lobes and clefts as shown in Figure 2 Hartel et al (2000) showed that the current can be explained using shallow-water theory if sufficiently accurate front conditions are prescribed for the nonhydrostatic flow at the head of the current.…”
Section: Review Of Previous Gravity Current Flow Studiesmentioning
confidence: 99%